Analysis of the machining accuracy when dry turning via experiments and finite element simulations - Aurich, Jan C.; Zimmermann, Marco; Schindler, Stefan; Steinmann, Paul (Production Engineering, 2013)
Workpiece and tool are subjected to severe mechanical and thermal loads when turning. These loads cause thermal expansions and mechanically induced deflections of the tool and the workpiece. Such deformations induce deviations from the nominal workpiece geometry. In order to decrease these deviations, the cutting condition needs to be optimized prior to actual machining. In this paper, the accuracy of machining when dry turning aluminum is analyzed via experiments and finite element simulations. For this purpose, seven characteristic values were used: the forces, the deflection of the workpiece, the quantity of heat in the workpiece, the temperature distribution in the workpiece, the temperature of the tool, the temperature of the tool holder, and the actual dimension of the workpiece after turning. These experimentally determined results serve in addition as boundary conditions for a 3D finite element model of the workpiece, which calculates the deformations of the workpiece. The continuous removal of material affecting the temperature distribution in the workpiece is considered. The actual dimensions of the workpiece after turning revealed a remarkable influence of the cutting condition used on the accuracy of machining. Differences of up to 116 μm regarding the deviation from the nominal workpiece diameter of 30 mm were observed. The analysis of the machining accuracy reveals that particularly the use of both high cutting speeds and feeds enhances the accuracy of machining when dry turning aluminum. © 2013 German Academic Society for Production Engineering (WGP).
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-TM.analys
Keywords: Cutting conditions; Deflections; Finite element simulation; Machining accuracy; Thermo-elastic deformations

Analysis of thermo-mechanical effects on the machining accuracy when turning aluminum alloys - Zimmermann, Marco; Schindler, Stefan; Steinmann, Paul; Aurich, Jan C. (Proceedings of the 9th International Conference on High Speed Machining, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-TM.analys

A thermo-viscoplastic constitutive law for isotropic hardening of metals - Schindler, Stefan; Steinmann, Paul; Aurich, Jan C.; Zimmermann, Marco (Archive of Applied Mechanics, 2016)
A novel empirical constitutive law for thermo-viscoplasticity is proposed, which considers isotropic strain and strain rate hardening as well as thermal softening. The yield stress considers strain rate and thermal effects independently for the initial yield stress and the (strain) hardening stress. To date, most plasticity models consider strain rate and temperature effects only combined for the initial and hardening stress, which is not sufficient for several materials. Seidt and Gilat (Int J Solids Struct 50(2):1781–1790, 2013) presented comprehensive experimental measurements for the aluminum alloy Al2024 including isothermal compression tests at low strain rates and various constant temperatures from room temperature to almost melting temperature as well as adiabatic compression tests at high strain rates (up to 10,900 s-1). In contrast to established thermo-viscoplastic material models, the proposed model is suitable to describe the material behavior of Al2024 accurately over a large range of loading conditions, i.e. from small to large plastic strains, low and high strain rates, and from room temperature to melting temperature, which is validated by the experimental data of Seidt and Gilat (2013). Consequently, with the use of the proposed constitutive law a variety of applications can be modeled, e.g. bulk forming, hot working, chip formation during cutting processes, or crash simulations. It is in particular promising for applications where combined loading conditions occur, like high strain rates and high temperatures at the chip formation.
Keywords: Strain hardening; Strain rate hardening; Thermal softening; Al2024

A two-scale simulation method accounting for thermal effects during turning - Schindler, Stefan; Zimmermann, Marco; Aurich, Jan C.; Steinmann, Paul (PAMM 2014, 2014)
During chip formation in turning processes, mechanical work is dissipated into thermal energy by plastic deformations and frictional processes. In case of dry cutting, the generated heat is in part removed with the chips while the rest flows into the tool and the workpiece. Within the latter, the temperature increases due to this heat flow, which in turn causes thermal expansions that increase the  cutting depth and thus induced eviations from the nominal workpiece geometry. These effects are treated separately by a local model for the chip formation and a global model for the whole workpiece in order to determine the temperature distribution inside the workpiece and the dependent thermal expansion
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-TM.atwosc_8

Drehen metallischer Verbundwerkstoffe - Zimmermann, Marco; Schindler, Stefan; Steinmann, Paul; Aurich, Jan C. (wt Werkstattstechnik - Online, 2014)
Werkstück und Werkzeug unterliegen während der Zerspanung einer thermischen Belastung. Diese bewirkt in Abhängigkeit zur Höhe der Belastung eine Abweichung zwischen nomineller und realer Schnitttiefe, wodurch die Fertigungsgenauigkeit negativ beeinflusst wird. In diesem Beitrag wird der Einfluss der Prozessparameter und der Verstärkungsphase metallischer Verbundwerkstoffe auf die thermischen Belastungen und die resultierenden Fertigungsgenauigkeiten analysiert.
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-TM.drehen

Effect of the cutting condition and the reinforcement of the MMC on the machining accuracy Drehen metallischer Verbundwerkstoffe: Einfluss von Prozessparametern und Verstärkungsphase auf die Fertigungsgenauigkeit - Zimmermann, M.; Schindler, Stefan; Steinmann, Paul; Aurich, J. C. (wt Werkstattstechnik - Online, 2014)
Workpiece and tool are subjected to thermal loads when turning. These loads that deform workpiece and tool cause a difference between the actual and the nominal depth of cut. The accuracy of machining is thus decreased. In this paper, the accuracy of machining is analyzed with regard to both the cutting condition (and hence the thermal loads) used for turning and the reinforcement of the metal matrix composite (MMC) in order to enhance the accuracy of machining in dry turning.
CRIS-Team Scopus Importer:2022-08-05

Effect of the cutting condition and the reinforcement phase on the thermal load of the workpiece when dry turning aluminum metal matrix composites - Aurich, Jan C.; Zimmermann, Marco; Schindler, Stefan; Steinmann, Paul (International Journal of Advanced Manufacturing Technology, 2015)
Aluminum metal matrix composites (Al-MMCs) are two-phase high-performance materials. The reinforcement of aluminum alloys enhances the properties of the composite material but leads to poor machinability. The required mechanical work for machining is mostly dissipated into heat. Considerable generated quantities of heat are therefore expected when machining Al-MMCs due to the poor machinability of these composite materials. The machine tool, the tool, and the workpiece are thus subjected to a thermal load, which decreases the accuracy of machining. The thermal load increases moreover when dry turning due to the missing heat convection through the cutting fluid. It is therefore necessary to investigate the effect of the reinforcement phase and the cutting condition used on the thermal load of the workpiece in dry turning. Therefore, composites with different reinforcement phases and the non-reinforced aluminum matrix were used as the workpiece materials. The reinforcement differs regarding the volume percent and the average size of the silicon carbide particulate reinforcements. The results revealed that the thermal load and the thermal expansion of the workpiece are significantly affected by the cutting condition used and the reinforcement phase. High cutting speeds and feeds and moderate depths of cut need to be used in order to decrease the thermal load of the workpiece. The Al-MMC workpieces are subjected to greater thermal loads than the workpieces of the non-reinforced alloy. However, better machining accuracies were achieved in dry turning the Al-MMCs.
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-TM.effect
Keywords: Aluminum metal matrix composite; Dry turning; Thermal load of the workpiece; Thermally induced deformation of the workpiece

Fertigungsgenauigkeit beim Drehen steigern - Einfluss der Prozessparameter auf die Maßhaltigkeit bei der Trockenbearbeitung - Aurich, Jan C.; Zimmermann, Marco; Steinmann, Paul; Schindler, Stefan (VDI-Z Integrierte Produktion, 2015)
Werkstück und Werkzeug erfahren während der spanenden Bearbeitung eine von der Belastungshöhe abhängige Wärmedehnung, welche die Maßhaltigkeit negativ beeinflusst. Um die Maßhaltigkeit zu verbessern, gilt es insbesondere bei der Trockenbearbeitung Prozessparameter zur Zerspanung einzusetzen, welche geringe Wärmeeinträge in das Werkstück und das Werkzeug verursachen. In diesem Beitrag werden Einflüsse der Prozessparameter auf die thermische Belastung und die Maßhaltigkeit des Werkstücks sowie eine simulationsgestützte Methode zur Prozessauslegung im Hinblick auf eine hohe Maßhaltigkeit vorgestellt.
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-TM.fertig

Finite element model to calculate the thermal expansion of the tool and the workpiece in dry turning - Schindler, Stefan; Zimmermann, Marco; Aurich, Jan C.; Steinmann, Paul (Proceedia CIRP, 2014)
Dry cutting is an important issue with regard to the economy and ecology of machining. The absence of the cutting fluid reduces both the costs for machining and the risk of ecological hazards. However, the missing convection through the cutting fluid increases the temperatures of the workpiece and the tool, and thus their thermal expansions. As a result, remarkable deviations from the nominal workpiece geometry occur. To enhance the accuracy of machining when dry turning, the thermal expansions of the tool and the workpiece can be calculated prior to actual turning using finite element (FE) models in order to adapt the nominal depth of cut accordingly. Therefore, an experimentally validated (using aluminum as the workpiece material) FE model is presented. The FE model inputs the heat flux into the tool and the workpiece as boundary conditions. The heat flux is applied locally and temporally discretized to the workpiece and the tool in the chip formation area. Their thermal expansions can thus be calculated in terms of the cutting condition used and the tool position, whereby process planning regarding the machining accuracy is facilitated. © 2014 Published by Elsevier B.V.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-TM.modeli
Keywords: Dry turning; Finite element; Thermal expansion

Identification of thermal effects on the diameter deviation of inhomogeneous aluminum metal matrix composite workpieces when dry turning - Schindler, Stefan; Zimmermann, Marco; Aurich, Jan C.; Steinmann, Paul (Production Engineering, 2015)
The use of dry cutting is associated with considerable thermal loads on the machine tool, the tool and the workpiece because of the missing heat convection through the cutting fluid. These thermal loads cause thermal expansions of the components. The accuracy of machining is thus decreased. In recent years, particularly the thermal expansions of the workpiece and the tool attained significance due to the increased demands on the machining accuracy. Aluminum metal matrix composites (Al-MMCs) show a poor machinability due to the reinforcement of light metal alloys via hard and abrasive materials. Dry turning of such composites is therefore accompanied with high thermal workpiece and tool loads. In this paper, finite element models of the workpiece and the tool are used in order to calculate the temperature distribution and thus the thermally induced expansion of the workpiece and the tool when turning AL-MMC regarding the cutting condition used. The removal of material and the heat flow to the environment are considered. The required boundary conditions (e.g. the heat flow into the workpiece) for the simulations were determined using experimental results. A new evaluation method of experimental diameter measurement validates the numerically calculated diameter deviations and reveals a considerable effect of the thermal expansions of the workpiece and the tool on the accuracy of machining.
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-TM.identi
Keywords: Thermo-elastic deformations; Aluminum metal matrix composite; Cutting condition; Machining accuracy; Finite element simulation

Numerical homogenization of elastic and thermal material properties for metal matrix composites (MMC) - Schindler, Stefan; Mergheim, Julia; Zimmermann, Marco; Aurich, Jan C.; Steinmann, Paul (Continuum Mechanics and Thermodynamics, 2016)
A two-scale material modeling approach is adopted in order to determine macroscopic thermal and elastic constitutive laws and the respective parameters for metal matrix composite (MMC). Since the common homogenization framework violates the thermodynamical consistency for non-constant temperature fields, i.e., the dissipation is not conserved through the scale transition, the respective error is calculated numerically in order to prove the applicability of the homogenization method. The thermomechanical homogenization is applied to compute the macroscopic mass density, thermal expansion, elasticity, heat capacity and thermal conductivity for two specific MMCs, i.e., aluminum alloy Al2024 reinforced with 17 or 30% silicon carbide particles. The temperature dependency of the material properties has been considered in the range from 0 to 500°C, the melting temperature of the alloy. The numerically determined material properties are validated with experimental data from the literature as far as possible.
Keywords: Numerical homogenization; Metal matrix composites; Thermomechanical; Material modeling

Thermo-elastic deformations of the workpiece when dry turning aluminum alloys - A finite element model to predict thermal effects in the workpiece - Schindler, Stefan; Zimmermann, Marco; Aurich, Jan C.; Steinmann, Paul (CIRP Journal of Manufacturing Science and Technology, 2014)
The workpiece is subjected to severe thermal loads when turning. These loads deforming the workpiece lead to a deviation between the actual and the nominal depth of cut. The accuracy of machining is thereby decreased. This paper presents a finite element technique to determine such thermal loads and deformations with regard to the cutting condition used and the actual tool position. The turning process can therefore be virtually optimized prior to actual turning in order to decrease thermally induced deformation of the workpiece. © 2014 CIRP.
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-TM.thermo
Keywords: Cutting condition; Finite element simulation; Machining accuracy; Thermo-elastic deformation